Poetics and politics of Sufism and Bhakti in South Asia : love, loss, and liberation - Kavita Panjabi Ed (Orient BlackSwan, 2011)
Contributed papers presented at a seminar on Feb. 8-10, 2006, organized by Assisatance for Strengthening of Infrastructure for Humanities and Social Sciences Program, Dept. of Comparative Literature, Jadavpur University, in collaboration with the Victoria Memorial Hall and others.